Telecommuting in the COVID – 19 Pandemic Situation in Thai Public Organizations - Panhomya, Kanyaphatr; Sangmahachai, Suwannee (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
The objectives of this research were to investigate the readiness of telecommuting in the COVID-19 pandemic situation in Thai public organizations and its effects on organizational productivity and personnel’s job satisfaction. The researcher adopted a multiple-case-study qualitative research methodology. The cases comprised 2 departments in the Ministry of Agriculture and Cooperatives (MOAC): the Office of the Permanent Secretary and Royal Irrigation Department (RID). Data collection included the conduct of in-depth interviews with 42 key informants as well as documentary research, participant observation and non-participant observation. Data were analyzed, classified, and synthesized across cases. The research findings were as the following: 1) The readiness of telecommuting in the COVID-19 pandemic situation in Thai public organizations comprised 5 components: (1) the readiness of organization’s leader in terms of decision-making and innovative leadership; (2) the readiness of organizational change; (3) the readiness of personnel’s telecommuting skills; (4) the readiness of organization’s technological support including hardware and secure connection; and (5) the readiness of telecommuting workplace. 2) The readiness of telecommuting had an effect on personnel’s job satisfaction. Jobs that were appropriate for telecommuting included those which could be replaced or supported by digital technology; for instance, approval or consultation tasks, service delivery, administrative and academic tasks. However, engineering and hydrology were considered unsuitable for telecommuting. Despite telecommuting has induced the lack of interaction among co-workers and supervisors, public organizations provided work supervision and monitoring, fair welfare and compensation, according to rules and regulations in times of teleworking. Explicit telecommuting policy and its regular policy revision had led to personnel’s job satisfaction. 3) The readiness of telecommuting had an effect on organizational productivity. Public organizations applied digital technology in order to reduce work processes and service time which resulted in customers’ satisfaction, budget savings and values. Consequently, telecommuting had an influence on public organizations’ efficiency and effectiveness; in other words, telecommuting caused organizational productivity. Article history: Received 15 March 2023 Revised 16 April 2023 Accepted 17 April 2023 SIMILARITY INDEX = 2.17%